The Performance of Selected Listed Firms in Jordan Between Two Crises - Yousef, Elham Mohammad Alhaj; Fseifes, Eman Abdel Khalik (International Journal of Economics and Financial Issues, 2022)
This study aims at investigating the impact of Covid-19 pandemic and Global Financial Crisis (GFC) on the performance of selected listed firms in Jordan. To achieve this objective, the study uses panel data for twenty firms over the period 2001-2020, obtained from Amman Stock Exchange database. All the study variables were found to be stationary at level, therefore, fixed and random effect models were applied to estimate two econometric equations with two performance indices. The results have revealed that both inflation and GFC have insignificant effect on the profitability of these firms, while debt ratio has a significant negative impact on their performance. The outcomes have also demonstrated the significant negative impact of Covid-19 pandemic on the profitability of such firms. Based on these results, the study has introduced some recommendations that may help in mitigating the adverse consequences of Covid-19 pandemic and in improving the profitability of Jordanian firms.